2002
DOI: 10.1073/pnas.052609899
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid hormone is a critical determinant for the regulation of the cochlear motor protein prestin

Abstract: CorrectionsBIOCHEMISTRY. For the article ''Differential effects of a centrally acting fatty acid synthase inhibitor in lean and obese mice,'' by Monica V. Kumar, Teruhiko Shimokawa, Tim R. Nagy, and M. Daniel Lane, which appeared in number 4, February 19, 2002, of Proc. Natl. Acad. Sci. USA (99, 1921-1925, the authors note the following. ''Under a licensing agreement between FASgen, Inc., and The Johns Hopkins University, Dr. Lane is entitled to a share of royalty received by the University on sales of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
112
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 44 publications
11
112
1
6
Order By: Relevance
“…The heads of up to 30 adult flies were pooled and stored at Ϫ70°C before use. mRNA was isolated and reverse-transcribed as described (19). By using the oligonucleotide primer DroF2 (5Ј-CAAAATGCCTAGT-GATAAAGAAAGTCCAG-3Ј), spanning the region from nucleotides 179,547-179,575 deduced from the original D. melanogaster CG5485 sequence (FlyBase FBgn0036770), in combination with either the downstream primer DroR2 (5Ј-CATATTCCACACAATCGTGCAGGGTG-3Ј, nucleotides 181,987-182,012) or DroEcoRVR (5Ј-AGAGGAAGGTA-GATATCCATGTGAAC-3Ј, nucleotides 181,308-181,333), a 2.21-kb and a 1.60-kb fragment of the CG5485 gene were amplified by PCR (annealing temperature, 55°C; number of cycles, 40).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heads of up to 30 adult flies were pooled and stored at Ϫ70°C before use. mRNA was isolated and reverse-transcribed as described (19). By using the oligonucleotide primer DroF2 (5Ј-CAAAATGCCTAGT-GATAAAGAAAGTCCAG-3Ј), spanning the region from nucleotides 179,547-179,575 deduced from the original D. melanogaster CG5485 sequence (FlyBase FBgn0036770), in combination with either the downstream primer DroR2 (5Ј-CATATTCCACACAATCGTGCAGGGTG-3Ј, nucleotides 181,987-182,012) or DroEcoRVR (5Ј-AGAGGAAGGTA-GATATCCATGTGAAC-3Ј, nucleotides 181,308-181,333), a 2.21-kb and a 1.60-kb fragment of the CG5485 gene were amplified by PCR (annealing temperature, 55°C; number of cycles, 40).…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were frozen immediately in liquid nitrogen. Tissues of six animals were pooled and mRNA was isolated and reverse-transcribed as described (19). By using the oligonucleotide primer DanF1 (5Ј-TGCAGCCATGGAGCACGTAACTGTTAG-3Ј) deduced from nucleotides 30,585-30,559 of the D. rerio genomic sequence z06s031971 (Ensembl Zebrafish Genome Browser, D. rerio, Assembly 06) together with the primer DanR4 (5Ј-CATCCCG-TATGAGATACCAGTGGACAC-3Ј, nucleotides 22,474 -22,500) and the primer combination DanF3 (5Ј-GTGTCCACT-GGTATCTCATACGGGATG-3Ј, nucleotides 22,474-22,500) and DanR1 (5Ј-ATGAGGTCAGGGGTCACAGGCTCACTG-3Ј, nucleotides 13,975-14,001), two overlapping fragments spanning 2,151 bp of coding sequence altogether were amplified by PCR (annealing temperature, 60°C; number of cycles, 40) and cloned as described for the Drosophila gene product CG5485.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of IHCs and OHCs in adult mice was evaluated by assessing the expression of KCNQ4 (15,16). Expression of the postsynaptic Ca 2ϩ -dependent potassium channel SK2, which transduces specific responses of efferent neurons to OHCs (17), and the motor protein prestin (18,19) was examined to prove a normal OHC phenotype. The observed subcellular distribution of the inwardly rectifying potassium channel subunit Kir4.1 in Deiters cells and the stria vascularis (20) and K v 3.1 in the stria vascularis and spiral ligament (21) suggested normal Deiters cell and stria vascularis phenotypes.…”
mentioning
confidence: 99%
“…Later studies have revealed that the most important transcriptional factor for prestin, the motor protein of outer hair cells in the cochlea, is regulated by thyroid hormones (42) and by TRb (43) . In addition, it has been shown that Kcnq4, a gene encoding an outer hair cell K channel protein, is regulated by TRa1 (43) , and that thyroid hormone regulates the expression of genes related to outer hair cell function, such as Tectb (44) .…”
Section: Genetic Factors Thyroid Metabolism and Auditory Functionmentioning
confidence: 99%